As comissões de heteroidentificação no desenvolvimento das políticas de ações afirmativas nos cursos de graduação da UNIPAMPA - Medina, Fabrício Pereira (2025)
Upon the tenth anniversary of Federal Law 12.711/2012, a broad public debate began evaluating its effects and proposing proposals to promote its renewal and improvement. Given the importance of this legislation for the reservation of places at Federal Universities and Institutes, this project aims to understand how the Affirmative Action Policy was implemented at the Federal University of Pampa and subsequently the implementation of the racial/ethnicity heteroidentification validation committee. It also analyzes the effectiveness and contribution of this policy against fraud and/or attempted fraud in the ethnic-racial subquotas allocated to Black, mixed race, and Indigenous students. This dissertation will delve deeper into the difficulties of access to higher education, especially at federal public institutions, for a Black population that for many years was excluded from society and discriminated against by a portion of the white population. It will also explore the struggles of Black social movements for democratization and socioeconomic equality in Brazilian society. For Severino (2008, p. 76), "the problems of Brazilian higher education cannot be addressed without considering the consolidation of the neoliberal capitalist societal project in our country at the beginning of this millennium." One form of historical reparation was the creation of laws and mechanisms to ensure Black people had greater representation in social circles and in politics within society. Concomitantly, discussions focused on the implementation of the heteroidentification committee and validation of self-declaration of race/ethnicity and its necessity to ensure that those entitled to affirmative action could apply for and enter university. As a multi-campus university, UNIPAMPA has 10 local heteroidentification committees and an institutional committee to analyze appeals filed by candidates rejected by the local committees. Finally, data collected from the admissions processes for seven highly competitive undergraduate programs were presented. The number of vacancies offered in each of the ethnic/racial modalities and whether the established phenotypic characteristics contemplate the fair evaluation by the members of the heteroidentification committee and validation of the candidate's self-declaration, whether in person or remotely.